KONSEP INSAN SALEH DALAM AL QURAN DAN TUJUAN PENDIDIKAN ISLAM: (Studi Tafsir Tematik) - Fahrudin Majid; Akhmad Alim (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
This study aims to understand and elaborate the meaning of Shalâh and pious man in the Qur'an and its relationship to the goals of Islamic education. Through a literature review using a qualitative research method with a thematic interpretation approach, referring to primary sources in the form of authoritative tafsir books, authoritative hadith commentary books, educational books and others, this study concludes that the goal of Islamic education is to form pious people physically and mentally, both pious personally, pious ritually and pious socially. With this piety, a human being will be able to carry out the task of his creation to realize worship and prosper the earth because he has a proper relationship with Allah, the universe, fellow human beings, with his worldly life and his future afterlife by upholding each principle of that relationship, which if condensed, the principle is the principle of justice, putting everything in its place, fulfilling rights to those who are entitled and acting correctly, appropriately and proportionally.